Gambaran Persepsi Ibu Hamil Tentang Skincare Yang Berbahaya Selama Kehamilan Di Puskesmas Boom Baru Palembang Tahun 2024 - Irmala Sari, Dessi; Oktari, Vivi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Skincare is a series of facial skin care treatments that aim to maintain health and improve the appearance of the skin, as well as address various skin problems. This treatment involves the use of various products that have specific functions, tailored to the type and condition of the skin. For pregnant women, choosing safe skincare is very important to maintain healthy skin and avoid harmful chemicals that can affect the health of the mother and baby.This study aims to identify pregnant women’s perceptions of dangerous skincare products during pregnancy at the Boom Baru Community Health Center in Palembang. The percentage of cosmetic use among pregnant women in Indonesia has not been specifically stated in the available information, but surveys indicate that more than 60% of pregnant women use various cosmetic products.This study uses a descriptive research design using a total sampling technique. Based on the results of the study conducted on 73 pregnant women, it can be concluded that the distribution of the characteristics of the respondents who were mostly aged 20-35 years as much as 100%, the second trimester of pregnancy as much as 53.5%, higher education as much as 95.5%, and working as much as 68%, the overview of knowledge about the use and skincare products is in the poor category as much as 68%. Based on the results of this study, there are still many pregnant women who do not know the skincare products for pregnant women. This research is expected to provide additional information for healthcare providers by providing health information about safe skincare products for pregnant women, thereby preventing potential risks.